Inhibitory effect of honey-sweetened goat and cow milk fermented with Bifidobacterium lactis Bb-12 on the growth of Listeria monocytogenes - Mirela Lučan; Vedran Slačanac; Jovica Hardi; Krešimir Mastanjević; Jurislav Babić; Vinko Krstanović; Marko Jukić (Mljekarstvo)
The aim of the study was to determine the influence of honey addition on fermentation of goat and cow milk with Bifidobacterium lactis Bb-12. Additionally, inhibitory potential of honey-sweetened fermented goat and cow milk against Listeria monocytogenes strain was examined. Two monofloral honey types, dark-colored chestnut and light-colored acacia honey were added. The basic hypothesis of this study was that addition of honey could have influence on the growth of Bifidobacterium lactis during the fermentation of goat and cow milk. Furthermore, higher inhibitory potential caused by honey addition against Listeria monocytogenes has been assumed. Compared to cow milk, higher acidity and CFU of Bifidobacterium lactis Bb-12 were noted in the fermented goat milk in all phases of the fermentation process. The results of this study show that both types of honey enhanced growth and acidity of the Bifidobacterium lactis Bb-12 in both milk types during fermentation. A disc assay has shown that development of growth inhibition zones depends on the type and concentration of honey, as well as on the milk type. The chestnut honey had generally higher inhibitory effect than acacia honey.